Strain-specific Plasmodium falciparum multifunctional CD4+ T cell cytokine expression in Malian children immunized with the FMP2.1/AS02A vaccine candidate. Issue 23 (17th May 2016) - Graves, Shawna F.; Kouriba, Bourema; Diarra, Issa; Daou, Modibo; Niangaly, Amadou; Coulibaly, Drissa; Keita, Yamoussa; Laurens, Matthew B.; Berry, Andrea A.; Vekemans, Johan; Ripley Ballou, W.; Lanar, David E.; et al.
Highlights: We demonstrate an AMA1-specific T cell response following vaccination. The antigen-specific immune response was detectable in an at-risk population in Mali. A differential pediatric immune response with clinical malaria vaccinees is shown. Abstract: Based on Plasmodium falciparum ( Pf ) apical membrane antigen 1 (AMA1) from strain 3D7, the malaria vaccine candidate FMP2.1/AS02A showed strain-specific efficacy in a Phase 2 clinical trial in 400 Malian children randomized to 3 doses of the AMA1 vaccine candidate or control rabies vaccine on days 0, 30 and 60. A subset of 10 Pf (−) (i.e., no clinical malaria episodes) AMA1 recipients, 11 Pf (+) (clinical malaria episodes with parasites with 3D7 or Fab9-type AMA1 cluster 1 loop [c1L]) AMA1 recipients, and 10 controls were randomly chosen for analysis. Peripheral blood mononuclear cells (PBMCs) isolated on days 0, 90 and 150 were stimulated with full-length 3D7 AMA1 and c1L from strains 3D7 (c3D7) and Fab9 (cFab9). Production of IFN-γ, TNF-α, IL-2, and/or IL-17A was analyzed by flow cytometry. Among AMA1 recipients, 18/21 evaluable samples stimulated with AMA1 demonstrated increased IFN-γ, TNF-α, and IL-2 derived from CD4 + T cells by day 150 compared to 0/10 in the control group ( p  < 0.0001). Among AMA1 vaccines, CD4 + cells expressing both TNF-α and IL-2 were increased in Pf (−) children compared to Pf (+) children. When PBMCs were stimulated with c3D7 and cFab9 separately, 4/18 AMA1 recipients with an AMA1-specific CD4 + response had a significant response to one or both c1L. This suggests that recognition of the AMA1 antigen is not dependent upon c1L alone. In summary, AMA1-specific T cell responses were notably increased in children immunized with an AMA1-based vaccine candidate. The role of CD4 + TNF-α + IL-2 + -expressing T cells in vaccine-induced strain-specific protection against clinical malaria requires further exploration. Clinicaltrials.gov Identifier:NCT00460525 .